Chief Wearing Frontlet - G.F. MacDonald (1972)
Gitksan, Gitseguecla village chief Ernest Hyzims in regalia. Note the cage of sea lion wiskers on top of his headress which would be filled with eagle down when he did a welcome dance for visitors to the village.